Determinación químico-bromatológica y actividad antimicrobiana de Spondias mombin L. (Ubo) - Arias A., Gladys (2000)
The specie Spondias mombin L. (Ubo), whose habitat is the tropics, grow to 1500 meter over the sea'level, it is also known as "Ubos", "Ciruelas agrias", "Tobo de montaña", "Shungu" y "Sheshon". It is a fruit which can be used as important source of nutrients. The bark extract shows antimicrobian activity for Staphylococcus aureus and Bacillus cereus. It also shows antifungus activity for Candida albicans.